Video Audio Hosting (Internet video, YouTube, Vimeo, Wistia marketing & training strategies) - Shanthini, Jennefer K (Recent Research Reviews Journal, 2023)
The objective of this study is to investigate the reasons for making online videos on platforms like Wistia, Twitch and YouTube. The available technologies and tools offered by the video sharing platforms have made the private online activities more professionalized. Even the practice of creating video content is becoming increasingly professionalized and commercialized. The motivations from outsides, which are frequently linked with work, i.e., the external factors are still more important for content creation than intrinsic motivations, which are connected to recreational work. This study illustrates how social impact affects the ideal subscription model for online video platforms. Paid, free, and trial strategies play the major role in choosing the strategy. Positive social influence and negative social influence are two cases provided by revenue models. This study summarizes the different video websites, relationship among the creators, and the online video which are analyzed in terms of its economics.